2016
DOI: 10.1039/c6ra16679b
|View full text |Cite
|
Sign up to set email alerts
|

Conduction mechanism model, impedance spectroscopic investigation and modulus behavior of the organic–inorganic [(C3H7)4N][SnCl5(H2O)]·2H2O compound

Abstract: In this study, the electric properties and modulus formulation of the compound [(C3H7)4N][SnCl5(H2O)]·2H2O were studied in the 200 Hz to 5 MHz frequency range and the 343–418 K temperature range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…7 (inset). The value of 's' for BF and BFCN decreases with increasing temperature, which implies that the polaron hopping mechanism took place between the potential barrier 57,58 . We have found that with the increase of temperature the value of hopping barrier energy (W H ) decrease and at the higher temperature small polaron tunneling is privileged due to higher internal energy of the particles (electronic Supplementary Information).…”
Section: Resultsmentioning
confidence: 96%
“…7 (inset). The value of 's' for BF and BFCN decreases with increasing temperature, which implies that the polaron hopping mechanism took place between the potential barrier 57,58 . We have found that with the increase of temperature the value of hopping barrier energy (W H ) decrease and at the higher temperature small polaron tunneling is privileged due to higher internal energy of the particles (electronic Supplementary Information).…”
Section: Resultsmentioning
confidence: 96%
“…We find that the modulus Nyquist plot exhibits a semicircle in all conditions, which represents that the relaxation is Debye-type in the crystal. It is reported that the correlation of the electrical modulus with impedance can determine the relaxation type either in localized (defect relaxation) or nonlocalized conduction (ionic or electronic conductivity). ,,, Consequently, the short-range and long-range movements of charge carriers can be distinguished by the M ″ and − Z ″ versus frequency plot. If the − Z max ″ and M max ″ peaks mismatch, then the charge carrier flow is of short range, while the matching of − Z max ″ and M max ″ peaks indicates the long-range flow. , Previously, Sheikh et al showed the presence of the localized relaxation process in the MAPbI 3 perovskite film by mismatch of − Z max ″ and M max ″ peaks .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Electrochemical modulus spectroscopy (MS) as derived from impedance spectroscopy has been widely used to investigate the dielectric behavior and charge-carrier relaxation mechanism in the SC, polycrystalline, and amorphous oxide materials. Previously, Wang et al investigated the dielectric properties of Ta-doped La 2 Ti 2 O 7 SC over a wide temperature range from 0–300 °C and in the frequency range of 10 2 to 10 5 Hz . Kim et al reported the MS of potassium lithium niobate (KLN) crystals in the frequency range from 100 Hz to 10 MHz and temperature range from 30 to 600 °C and showed that the dielectric relaxation behavior is fitted to the Kohlrausch–Williams–Watts exponential function .…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of the alternating current reveals the presence of a thermally activated process caused by the increase in the energy of the charge carrier. 41 As indicated by Jonscher’s universal power law, electrical conductivity can be described by: 42 σ ToT = σ DC + Aω n …”
Section: Resultsmentioning
confidence: 99%